(untitled) - Sharma, Anuj Ram (Academia Anatomica International, 2019)
Introduction: The Thyroid gland is a highly vascular gland placed anteriorly in the neck, extending from the level of fifth cervical vertebra to first thoracic vertebra.The lobes of gland are conical. Their apices diverge laterally to the oblique line on the lamina of thyroid cartilage, and their bases are at the level of 4th or 5th tracheal ring. The relationship of the superior thyroid artery to the external laryngeal nerve is important to the surgeon during thyroid surgery.The artery and nerve are close to each other higher up but diverge near the gland. Thus in order to avoid injury to the external laryngeal nerve, the superior thyroid artery is ligated as near to the gland as possible. Subjects and Methods: This study was conducted on 50 cadavers of known age and sex in the dissection laboratory, department of anatomy. The cadavers were embalmed through carotid arterial perfusion or femoral arterial perfusion. Results: The site of the origin of the superior thyroid artery (STA) was evaluated as it arose from external carotid artery in 66% cases, from carotid bifurcation in 33% cases and from common carotid artery in 1% cases.The site of the origin of the superior thyroid artery (STA) was evaluated as it arose from external carotid artery in 66% cases, from carotid bifurcation in 33% cases and from common carotid artery in 1% cases.The evaluation of distance from upper pole of the thyroid gland to the level where External superior laryngeal nerve turns medially from Superior thyroid artery was found More than 1 cm in 73% cases & Less than 1 cm in 27% cases. Conclusion: The relationship of superior thyroid artery to external superior laryngeal nerve is very important for surgeons during thyroid surgeries to avoid injuries to above nerves while ligating STA.